Assessment of α-amanitin toxicity and effects of silibinin and penicillin in different in vitro models. (September 2020) - Popp, Tanja; Balszuweit, Frank; Schmidt, Annette; Eyer, Florian; Thiermann, Horst; Steinritz, Dirk
Abstract: Silibinin (Sil) is used as hepatoprotective drug and is approved for therapeutic use in amanitin poisoning. In our study we compared Sil-bis-succinate (SilBS ), a water-soluble drug approved for i.v.-administration, with Sil solved in ethanol (SilEtOH ), which is normally used in research. We challenged monocultures or 3D-microtissues consisting of HepG2 cells or primary hepatocytes with α-amanitin and treated with SILBS, SILEtOH, penicillin and combinations thereof. Cell viability and the integrity of the microtissues was monitored. Finally, the expression of the transporters OATP1B1 and B3 was analyzed by qRT-PCR. We demonstrated that primary hepatocytes were more sensitive to α-amanitin compared to HepG2. Primary hepatocytes cultures were protected by SilBS and SilEtOH independent of penicillin from the cytotoxic effects of α-amanitin. Subsequent studies of the expression profile of the transporters OATP1B1/B3 revealed that primary hepatocytes do express both whereas in HepG2 cells they were hardly detectable. Our study showed that SilBS has significant advantage over SilEtOH with no additional benefit of penicillin. Moreover, HepG2 cells may not represent an appropriate model to investigate Amanita phalloides poisoning in vitro with focus on OATP transporters since these cells are lacking sensitivity towards α-amanitin probably due to missing cytotoxicity-associated transporters suggesting that primary hepatocytes should be preferred in this context. Highlights: Water-soluble formulation SilBS is better tolerated than the EtOH-solved silibinin. Primary hepatocytes represent a more appropriate model than HepG2 cells. Cells in a complex 3D-spheroid seem to mimic the in vivo situation more closely. Spheroid analysis support all efforts to prevent animal tests following the 3R rules.